Applications of halophilic enzymes in the pharmaceutical industry and medicine - Velankar, Radhika; Shinde, Vinaya; Kothari, Mukta; Gunjal, Aparna (Nepal Journal of Environmental Science, 2025)
Halophiles are an important group of microorganisms that can grow under high salt conditions. The paper here describes the enzymes of halophiles and their mode of action. The application of halophiles in industries is also covered. The halophilic microorganisms have immense significance; hence, this paper describes the halophilic microorganisms and their enzymes. The paper highlights mainly the enzymes, i.e., cellulase, esterase, lipase, protease, laccase, L-asparaginase, and L-glutaminase from halophiles, which have industrial applications, and the study of these enzymes is very important.